TINDAK TUTUR DIREKTIF DALAM PAPAN PERINGATAN DI RINKU TOWN OSAKA JEPANG - Muhlisian, Asep Achmad (Jurnal SORA - Pernik Studi Bahasa Asing, 2023)
This study discusses directive speech acts on warning boards in the Rinku Town area, Osaka, Japan with the aim of describing the form and function of directive speech acts and the factors that influence them. The method used is descriptive and data collection techniques in this study using documentation, observation and note-taking techniques. The results of the data analysis show that directive speech acts in the form of prohibitions and orders are more dominant than requests, expectations and solicitations. Speeches on warning boards are made in the form of directive speech acts, prohibitions or orders, especially posted in places that are considered dangerous or can disturb the comfort of others, especially in public places.